2017
DOI: 10.1515/cerce-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Seed Yield of Hybrid Rice by Maintaining Row Ratio and Dosages of Gibberellic Acid

Abstract: ABSTRACT. The purpose of this study was to identify the optimum levels of gibberellic acid and suitable row ratio for maximization the seed yield of hybrid rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
3
0
0
Order By: Relevance
“…Combination between cytokines and mol bedim are plant hormones that regulate various processes of plant growth and development, which are particularly important in cell elongation (Hedden and Phillips, 2000). The results agree with those reported by Rahman et al (2010) and Abo-Youssef et al (2017). The variation between the CMS lines could be attributed to the difference in genetic background.…”
Section: Discussionsupporting
confidence: 90%
“…Combination between cytokines and mol bedim are plant hormones that regulate various processes of plant growth and development, which are particularly important in cell elongation (Hedden and Phillips, 2000). The results agree with those reported by Rahman et al (2010) and Abo-Youssef et al (2017). The variation between the CMS lines could be attributed to the difference in genetic background.…”
Section: Discussionsupporting
confidence: 90%
“…Combining a plant ratio of 20 cm x 20 cm (P1R4) with a row ratio of 2R:14A gave the highest seed yield compared to other treatment combinations, followed by P2R4 combination which gave a good SY with no significant difference with that of P1R4. These results are in line with (Abo-Youssef et al, 2017) reported that the highest F1 seed yield was achieved at a higher ratio of A-lines, while the lowest yields of the P3R1 treatment combination was a combination of 15 cm x 15 cm plant ratio treatment with a row ratio of 2R:8A (Figure 1). This study provides information that planting density combined with spacing and row ratio of CMS provides different seed yields.…”
Section: Effects Of Interactionsupporting
confidence: 91%
“…In this respect, the exogenous application of GA 3 uniquely or in combination with NAA and IAA exhibited a significant increase in panicle length and panicle exertion compared to untreated plants. Similar significant positive impacts of growth regulators on panicle length panicle exertion were disclosed by Abo-Youssef et al [ 25 ], Hasan et al [ 26 ], and Pin et al [ 27 ]. Likewise, Huang et al [ 28 ] assessed the impact of IAA; NAA; indole-3-butyric acid; 2,4-dichloro-phenoxy acetic acid; 3,6-dichloro-2-methoxy-benzoic acid; and abscisic acid on the floret closure of diverse rice genotypes.…”
Section: Discussionsupporting
confidence: 79%